Exploring differences in adolescents' educational expectations: a structural equation modeling approach - Wood, Valerie Ford, author; Bell, Paul A., advisor; Edwards, Ruth W., advisor; Swaim, Randall C., committee member; Dik, Bryan J., committee member; Most, David E., committee member (Colorado State University. Libraries, 2010)
The current study examined a number of influences that are theorized to affect adolescents' educational expectations, including socio-economic status, perceived barriers to success, peer factors, family influences, school performance, and school adjustment. This study utilized a subset of pre-existing data, with the subset consisting of 76,218 students who completed the Community Drug and Alcohol Survey as part of a stratified random sample of junior high schools throughout the United States. The hypotheses were tested using structural equation modeling. The major findings were that Perceived Family SES was related to Resource Barriers, Resource Barriers was related to School Performance, Friends' School Adjustment was related to School Adjustment, Family Academic Support was related to School Adjustment, Friends' School Performance was related to School Performance, School Adjustment was related to School Performance, Family Academic Support was related to Educational Expectations, and School Performance was related to Educational Expectations. The measurement model results indicated that the latent construct of Perceived Barriers was more appropriately considered to be several distinct latent constructs. When this revision was taken into account, the measurement model achieved adequate fit (Robust NFI = .901, Robust CFI - .902). The structural equation model results found that the Perceived Barrier items may have been interpreted differently by the students than intended, with minority students in particular interpreting those items differently. While the peer constructs operated as hypothesized, the structural model achieved a better fit when Family Academic Support rather than School Performance, was used as a predictor of School Adjustment. Overall, the proximal indicator of Educational Expectations in the current study was School Performance. The initial structural model achieved a fit of Robust NFI = .811, Robust CFI = .812, and the revised structural model achieved improved fit at a level of Robust NFI = .859, Robust CFI = .860. While the current study is limited by a number of factors, the results are in agreement with findings from previous literature, and indicate that School Performance may be more important to understanding adolescents' Educational Expectations than previously acknowledged.
Keywords: structural equation modeling; gender; adolescents; ethnicity; educational expectations; Educational attainment -- United States; Education, Secondary -- Social aspects -- United States -- Cross-cultural studies; Structural equation modeling -- Education; Minority students -- United States -- Attitudes